Depression treatment preferences by race/ethnicity and gender and associations between past healthcare discrimination experiences and present preferences in a nationally representative sample. (May 2020) - ,; Soffer, Tali Fleitman; Chambers, Valeria; Quinerly, Catherine Rodriguez; Mann, Ziva; Nabisere, Ruth; Shaikh, Farah N.; Jordan, Dierdre; Moradi, Afsaneh; de Castro, Selma; Abolaban, Heba; Lee, Esther; et al.
Abstract: Background: Depression treatment disparities are well documented. Differing treatment preferences across social groups have been suggested as a cause of these disparities. However, existing studies of treatment preferences have been limited to individuals currently receiving clinical care, and existing measures of depression treatment preferences have not accounted for factors that may be disproportionately relevant to the preferences of disparities populations. This study therefore aimed to assess depression treatment preferences by race/ethnicity and gender in a representative community sample, while accounting for access to healthcare, provider characteristics, and past experiences of discrimination in healthcare settings. Methods: We conducted a nationally representative study of individuals with depression in and out of clinical care. Treatment preferences (medication versus talk therapy) were elicited through a discrete choice experiment that accounted for tradeoffs with factors related to access and provider characteristics deemed relevant by community stakeholders. Past discrimination was assessed through questions about unfair treatment from medical providers and front desk staff due to personal characteristics (e.g., race, gender). We used conditional logit models to assess treatment preferences by race/ethnicity and gender and examined whether preferences were associated with past experiences of healthcare discrimination. Results: Non-Hispanic white respondents (OR—here, the odds of a talk therapy preference over the odds of a medication preference: 0.80, 95% CI: 0.64, 0.99) and men (OR 0.76, 95% CI: 0.60, 0.96) preferred medication over talk therapy, while non-Hispanic black respondents, Hispanic respondents, and women did not prefer one over the other. Past discrimination in healthcare settings was associated with lower preferences for talk therapy and greater preferences for medication, particularly among non-Hispanic black respondents and women respondents. Conclusions: Addressing previous methodological limitations yielded estimates for depression treatment preferences by race/ethnicity and gender that differed from past studies. Also, past discrimination in healthcare settings was associated with current treatment preferences. Highlights: Non-Hispanic whites and men with depression preferred medication over talk therapy. Racial/ethnic minorities and women did not prefer one treatment over the other. Many racial/ethnic minorities with depression had faced healthcare discrimination. Past healthcare discrimination was associated with a preference for medication.